The Psychology of Decision Making : People in Organizations. - Beach, Professor Lee Roy R. (Foundations for organizational science., 2005)
The Psychology of Decision Making provides an overview of decision making as it relates to management, organizational behavior issues, and research. This engaging book examines the way individuals make decisions as well as how they form judgments privately and in the context of the organization. It also discusses the interplay of group and institutional dynamics and their effects upon the decisions made within and on the behalf of organizations.